Bolboceras bilaspuricans (Coleoptera: Geotrupidae: Bolboceratinae), a new species from Chhattisgarh, India - Gupta, Devanshu; Chandra, Kailash (Zootaxa, 2016)
Bolboceras bilaspuricans Gupta & Chandra, new species (Coleoptera: Geotrupidae: Bolboceratinae), from the Chhattisgarh state, India is described, diagnosed, and illustrated. The new species is classified in the B. nigricans species group of the genus Bolboceras Kirby, 1819. The new species is morphological similar to Bolboceras malabaricum Krikken, 2013 from southwestern India.